Current knowledge on correlations between highly prevalent dental conditions and chronic diseases: an umbrella review - Seitz, Max; Listl, Stefan; Bartols, Andreas; Schubert, Ingrid; Blaschke, Katja; Haux, Christian; Zande, Marieke M. van der (Preventing Chronic Disease, 2019)
Preventing Chronic Disease (PCD) is a peer-reviewed electronic journal established by the National Center for Chronic Disease Prevention and Health Promotion. PCD provides an open exchange of information and knowledge among researchers, practitioners, policy makers, and others who strive to improve the health of the public through chronic disease prevention.
Gesehen am 30.09.2019